Beyond Biopolitics : Theory, Violence, and Horror in World Politics. - Debrix, Francois (Interventions., 2011)
Beyond Biopolitics exposes the conceptual limits of critical biopolitical approaches to violence, war, and terror in the post-9/11-War on Terror era. This volume shows that such popular international political theories rely upon frames of representation that leave out of focus a series of extreme forms of gruesome violence that have no concern for the preservation of life, a crucial biopolitical theme. Debrix and Barder mobilize different concepts--horror, agonal sovereignty, the pulverization of the flesh, or the notion of an inhumanity-to-come--to shed light on past and present ghastly scene.